176k views
5 votes
2x+5-3x=8(x+1); solve for x.

User Mohab
by
6.4k points

2 Answers

0 votes

We are given:

2x + 5 - 3x = 8(x + 1)

We can start with several things. First, we can combine the x terms on the left side of the equation, and apply the distributive property on the right side of the equation.

5 - x = 8x + 8

Now, we can add x to both sides, and subtract 8 from both sides to isolate the variable.

5 - x = 8x + 8

-8 + x + x -8

We end up with:

9x = -3

By dividing both sides by 9, we get x =
-(1)/(3).

If you want to check your answer, just plug x in!

2(
-(1)/(3)) + 5 - 3(
-(1)/(3)) = 8(
-(1)/(3) + 1)


-(2)/(3) + 5 + 1 =
-(8)/(3) + 8


-(2)/(3) +
(18)/(3) =
-(8)/(3) +
(24)/(3)


(16)/(3) =
(16)/(3)

As you can see,
(16)/(3) =
(16)/(3) as a result of having x =
-(1)/(3).

User Nafeo Alam
by
6.1k points
2 votes

First you must distribute the 8 to the numbers inside the parentheses

2x + 5 - 3x = 8 (x + 1)

2x + 5 - 3x = 8*x + 1*8

2x + 5 - 3x = 8x + 8

Now you must combine like terms (let's first start with the like terms on the left side). This means the numbers with the same variables must be combined...

-3x + 2x = -x

so...

-x + 5 = 8x + 8

Now you must combine like terms by combining -x with 8x. To do this first add 1x to both sides (what you do on one side you must do to the other). Since x is negative on the left side, addition (the opposite of subtraction/negative) will cancel it out (make it zero) from the left side and bring it over to the right side.

-x + x + 5 = 8x + x + 8

0 + 5 = 9x + 8

5 = 9x + 8

Now bring 8 to the left side by subtracting 8 to both sides (what you do on one side you must do to the other). Since 8 is being added on the right side, subtraction (the opposite of addition) will cancel it out (make it zero) from the right side and bring it over to the left side.

5 - 8 = 9x + 8 - 8

-3 = 9x

Next divide 9 to both sides to finish isolating x. Since 9 is being multiplied by x, division (the opposite of multiplication) will cancel 9 out (in this case it will make 9 one) from the right side and bring it over to the left side.

-3/9 = 9x/9

x =
(-1)/(3)

Hope this helped!

~Just a girl in love with Shawn Mendes

User Joshs
by
6.2k points